Education of Mother Milk Companion Food (MP-ASI) According to Balanced Nutrition Guidelines - Aulia, Fika; Lestari, Pratiwi P; Ulfah, Bardiati (UrbanGreen Central Media, 2021)
After the baby is 6 months old, breast milk can no longer provide adequate nutrition. For sufficient the nutrition, baby needs mother milk companion food (MPASI). During the age of 6-24 months, that’s a period that is vulnerable to malnutrition. So that in providing MPASI, it must balanced nutritional guidelines: protein, fat and carbohydrates. The fact that occurs is that the practice of giving mother milk companion food is not appropriate, like early feeding before 6 months, the food given does not vary, limited to carbohydrates only rice, vegetables and fruit are rarely given, increase animal protein. The purpose of this community service is to increase understanding of the practice of giving milk companion food according to balanced nutrition guidelines. The method uses education and evaluated them. The results is education can increase the knowledge and commitment of participants by giving milk companion food according to balanced nutrition guidelines.